Metode Bercerita Membentuk Kepribadian Muslim pada Anak Usia Dini - Muzdalifah, Muzdalifah (THUFULA, 2013)
Early childhood is a sensitive period. All potential can be developedthrough education at an early age. The world of children is a world of imagination.By using their imagination, story-telling method about struggles, worships, orRasulullah and his companions’ behavior Rasullah that must be followed is veryappropriate for growing social values , moral, spiritual, which is expected to buildthe Muslim personality.